Scientific Interpretation of the Problem of Communication in the Works of Eastern Thinkers - Eshtilovov, S. (International Journal on Human-Computing Studies, 2023)
In the article, the opinions of Eastern thinkers on behavior and communication are put forward. In addition, the views of Eastern communist scholars such as Muhammad ibn Musa al-Khorazmi, Abu Nasr Farabi, Abu Rayhan Beruni, Abu Ali ibn Sina, Yusuf Khos Khajib, Kaikovus, etc., were analyzed.